Shape of Atlantic Tropical Cyclone Tracks and the Indian Monsoon. Issue 19 (10th October 2018) - Kelly, Patrick; Leung, L. Ruby; Balaguru, Karthik; Xu, Wenwei; Mapes, Brian; Soden, Brian
Abstract: We find a significant enhancement of the North Atlantic subtropical high on interannual timescales (1970–2016) concurrently linked to an anomalously strong Indian monsoon in September. Consistent with a stronger North Atlantic subtropical high, enhanced anticyclonic flow and subtropical easterlies in the eastern Atlantic basin are found during strong monsoon years. Observational regression analysis combined with a statistical track model are used to assess the influence of these monsoon‐linked wind variations on Atlantic tropical cyclone (TC) tracks originating in the main development region. When controlling for effects of El Niño–Southern Oscillation (ENSO), a westward shift of TC tracks is shown to be robustly correlated to internal monsoon variability in September. This work highlights variability of the Indian monsoon as an additional constraint on Atlantic TCs, with increased landfall probability during a strong monsoon. Previous attribution of similar steering effects to ENSO need to be reconsidered to account for ENSO's correlation with the monsoon. Plain Language Summary: Variations of tropical cyclone or hurricane impacts (such as landfall probability) depend on steering effects, in addition to effects that govern their intensity or frequency. These steering effects are a key factor governing where hurricanes go after they form. For the first time, we use observations and modeling evidence to show that year‐to‐year variations of tropical cyclone steering effects in the Atlantic are related to the Indian monsoon. This is because monsoon heating from rainfall drives the large‐scale counterclockwise circulation in the Atlantic known as the North Atlantic subtropical high. When the monsoon is stronger, the subtropical high is stronger, which means enhanced flow from the east steers tropical cyclones more strongly westward in the Atlantic. An implication of these results is an increase likelihood of landfalling hurricane events during a strong monsoon, after controlling for other factors. These results also challenge a prevailing notion that La Niña events cause more landfalling hurricanes due to steering changes. Our analysis suggests that causality inference may partially be happenstance, since a strong Indian monsoon often occurs during La Niña events. Key Points: A monsoon‐enhanced subtropical high dictates a westward shift of Atlantic tropical cyclones in observations and in a statistical track model Interannual variations in steering effects are due to internal Indian monsoon variability, independent of ENSO Previous changes in steering and landfall probability attributed to ENSO need to account for ENSO's correlation to the Indian monsoon